Program Bimbingan Akademik Untuk Meningkatkan Motivasi Belajar Peserta Didik - Evitarini, Anggi (Pusat Kajian Bimbingan dan Konseling FIPPS Unindra, 2018)
This research is motivated because the students' learning problems cannot be completed well by the teachers. The purpose in this study to test the effectiveness of academic guidance programs to increase students' learning motivation. The results of trials when the research was conducted showed that the tutoring program was proven to be able to increase students' learning motivation. Thus, tutoring programs can be applied by teachers to increase students' learning motivation.